Where to Create Jobs to Reduce Poverty : Cities or Towns? - Christiaensen, Luc; De Weerdt, Joachim; Kanbur, Ravi (World Bank, Washington, DC, 2017)
Should public investment be targeted to big cities or to small towns, if the objective is to minimize national poverty? To answer this policy question, this paper extends the basic Todaro-type model of rural-urban migration to the case of migration from rural areas to two potential destinations, secondary town and big city. The analysis first derives the labor income, migration cost and poverty line conditions under which a poverty gradient from rural to town to city will exist as an equilibrium phenomenon. Then sufficient statistics are developed for the policy decisions based on these parameters. The empirical remit of the model is illustrated with long-running panel data from Kagera, Tanzania. Further, the paper shows that the structure of the sufficient statistics is maintained in the case where the model is generalized to introduce heterogeneous workers and jobs.